2021
DOI: 10.1111/ijcp.14550
|View full text |Cite
|
Sign up to set email alerts
|

Multiple vertebral fractures after suspension of denosumab. A series of 56 cases

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In post hoc analyses of the FREEDOM and FREEDOM extension studies prevalent vertebral fractures, longer time off treatment, greater gain in hip BMD on treatment, and greater loss in hip BMD off treatment were identified as risk factors for multiple vertebral fractures ( Cummings et al, 2018 ; McClung et al, 2017 ). In addition, observational studies have identified younger age ( Solling et al, 2020 ) and longer treatment duration ( Anastasilakis et al, 2017 ; Sosa-Henríquez et al, 2021 ) as risk factors for vertebral fractures. The patient in the present case study was relatively young and had been treated with denosumab for five years without any prior observations of vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In post hoc analyses of the FREEDOM and FREEDOM extension studies prevalent vertebral fractures, longer time off treatment, greater gain in hip BMD on treatment, and greater loss in hip BMD off treatment were identified as risk factors for multiple vertebral fractures ( Cummings et al, 2018 ; McClung et al, 2017 ). In addition, observational studies have identified younger age ( Solling et al, 2020 ) and longer treatment duration ( Anastasilakis et al, 2017 ; Sosa-Henríquez et al, 2021 ) as risk factors for vertebral fractures. The patient in the present case study was relatively young and had been treated with denosumab for five years without any prior observations of vertebral fractures.…”
Section: Discussionmentioning
confidence: 99%
“…A further study of 56 patients with vertebral fractures post discontinuation of denosumab found that the median time to fracture was 11 months after the last dose of denosumab 4 . This equates to 5 months after the date a further dose was due to be given.…”
Section: Considerations Before Starting a Course Of Denosumab Therapymentioning
confidence: 99%
“…They also found a statistically significant association of duration of treatment with denosumab and the rate of vertebral fracture with an 11% risk of vertebral fracture for every year of denosumab use. 4…”
Section: Considerations Before Starting a Course Of Denosumab Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…This increased fracture risk may begin as soon as 2 months after the first missed denosumab dose ( Cummings et al, 2018 ; Florez et al, 2019 ; Burckhardt et al, 2021 ). Moreover, the rebound fracture risk may increase with a longer duration of denosumab treatment prior to discontinuation ( Anastasilakis et al, 2021 ; Sosa-Henríquez et al, 2021 ; Popp et al, 2018 ); cumulative exposure effects may thus need to be considered in drug effects studies of denosumab discontinuation.…”
Section: Pharmacology Of Osteoporosis Medicationsmentioning
confidence: 99%